New reactions of titanium imido and hydrazido complexes - Stevenson, L (2015)
This Thesis reports the synthesis and reactions of titanium-nitrogen multiply bonded compounds. Reactions with both acidic and hydridic element-hydrogen bonds are explored along with unsaturated small molecules in general. Chapter One provides a background on imido and hydrazido complexes, starting with the relevance of the hydrazido ligand to nitrogen fixation. Group 4 alkylidene hydrazide and alkoxyimide complexes are also reviewed. The Chapter focuses in particular on the synthesis, structure, and stoichiometric and catalytic reactions of these complexes with unsaturated substrates. Chapter Two describes the synthesis of new titanium imido complexes and the reactions with molecules containing N–H or O–H bonds, internal alkynes and nitriles. The analogous reactions of the hydrazido compound Ti(N2iPrNMe)(NNPh2)(py) are also investigated. Chapter Three details the reactions of the imido compound Ti(N2iPrNMe)(NXyl)(py) with terminal alkynes. Unusual reaction products are described and a full mechanistic study into their formation along with their synthesis and characterisation is presented. In addition, the relevance of these reactions to the catalytic hydrohydrazination of terminal alkynes and diphenylhydrazine with Ti(N2iPrNMe)(NNPh2)(py) is discussed. Chapter Four describes the reactivity of the hydrazido compound Ti(N2iPrNMe)(NNPh2)(py) with a range of silanes and boranes. These reactions are then explored through an in-depth experimental and computational study. Chapter Five presents full experimental procedures and characterising data for the new complexes reported.